2007
DOI: 10.1037/0022-0663.99.3.653
|View full text |Cite
|
Sign up to set email alerts
|

Behavior problem trajectories and first-grade cognitive ability and achievement skills: A latent growth curve analysis.

Abstract: Using data from the National Institute of Child Health and Human Development Study of Early Child Care and Youth Development, the authors investigated whether there was evidence of intraindividual stability in behavior problems over time as well as whether children with higher levels of behavior problems at 24 months and more rapid increases in behavior problems prior to school entry performed more poorly on 1st-grade tests of cognitive ability and achievement than their peers. Three findings were noteworthy. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
110
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 143 publications
(115 citation statements)
references
References 76 publications
5
110
0
Order By: Relevance
“…Replication of this study among children living in urban London (see Berger et al 1975) found an even higher rate of co-occurrence, with nearly half of children having reading difficulties scoring above cutoffs for antisocial behavior on teacher ratings. A recent study (Bub et al 2007) found that children exhibiting high levels of externalizing problems at 24 months of age had lower scores on achievement in first grade. Further, Heiervang et al (2001) found that children with poor reading skills had more parent and teacher-reported aggressive behavior than children without reading problems.…”
mentioning
confidence: 97%
“…Replication of this study among children living in urban London (see Berger et al 1975) found an even higher rate of co-occurrence, with nearly half of children having reading difficulties scoring above cutoffs for antisocial behavior on teacher ratings. A recent study (Bub et al 2007) found that children exhibiting high levels of externalizing problems at 24 months of age had lower scores on achievement in first grade. Further, Heiervang et al (2001) found that children with poor reading skills had more parent and teacher-reported aggressive behavior than children without reading problems.…”
mentioning
confidence: 97%
“…Externalizing behaviors are associated with lower achievement scores (Bub, McCartney, & Willett, 2007) and poor school adjustment (Fantuzzo, Sekino, & Cohen, 2004). Left unaddressed, early behavior problems are linked to an increased risk for school suspensions (Reinke et al, 2008) and dropout (Vitaro, Brendgen, Larose, & Tremblay, 2005), aggression (Fantuzzo et al, 2004), and adult mental health disorders (Reef, Diamantopoulou, van Meurs, Verhulst, & van der Ende, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Approximately one third of children who display high levels of early externalizing behavior problems continue on a trajectory of problem behavior through adolescence (Loeber, Farrington, & Waschbusch, 1998;Losel & Bender, 2003. Young children who display high levels of early externalizing behavior problems are also at risk for a host of subsequent academic issues, including school retention, school dropout, and lower school engagement (Bub, McCartney, & Willett, 2007;Bulotsky & Fantuzzo, 2011;Duncan & Magnuson, 2011;Fantuzzo et al, 2007;Raver, 2002). Furthermore, externalizing behavioral concerns in early primary classrooms take up significant portions of teachers' time and efforts, thereby undermining the learning experience for all students (Houts, Caspi, Pianta, Arseneault, & Moffitt, 2010).…”
Section: Introductionmentioning
confidence: 99%